Anode for PEM water electrolyser as well as preparation method and application of anode

CN119956404APending Publication Date: 2025-05-09THE UNIVERSITY OF HONG KONG
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311468368.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-11-07
Publication Date
2025-05-09

AI Technical Summary

Technical Problem

The cost of using existing PEM water electrolytic cells is high, mainly due to the high prices of precious metal catalysts and pure titanium electrodes, and the unstable and easy corrosion of traditional anodes in a strongly acidic environment.

Method used

By performing surface thermal oxidation treatment on the manganese-containing stainless steel matrix material, a layered oxide structure is formed, including crystalline manganese oxide and amorphous iron-containing manganese oxide, as the anode of the PEM water electrolytic cell. The anode has good catalytic activity and stability in an acidic environment.

Benefits of technology

It significantly reduces the equipment cost and operating costs of PEM water electrolytic cell, improves the corrosion resistance and OER catalytic activity of the anode, and can work stably in a strong acid medium with high applied potential, extending its service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119956404A_ABST
    Figure CN119956404A_ABST
Patent Text Reader

Abstract

The invention provides an anode for a PEM water electrolyser and a preparation method thereof, the anode comprises a stainless steel substrate and a layered oxide structure generated on the surface of the stainless steel substrate in situ, and the layered oxide structure comprises crystal manganese oxide and amorphous iron-containing manganese oxide. The layered oxide structure on the surface of the anode can keep long-time water electrolysis catalytic activity and stability under the acidic condition, and the problems of corrosion and stability of autocatalytic and non-noble metal electrodes under the acidic environment are solved through proper surface structure component selection. According to the anode, the cost of hydrogen production based on a noble metal catalyst at present is remarkably reduced, and the problem of high cost of PEM large-scale electrolytic hydrogen production is expected to be solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an anode for a PEM water electrolyzer and a preparation method and application thereof. Background Art

[0002] In line with the rapid development of the low-carbon economy and the inevitable trend of global "carbon neutrality", hydrogen energy with extremely low carbon emissions is expected to replace fossil fuels and become one of the most important energy storage materials in the future. Hydrogen is a clean and green energy carrier with a high specific heat capacity, suitable for storing intermittent renewable energy. In recent years, water electrolysis has become an attractive and rapidly growing method for hydrogen production because the only byproduct is harmless oxygen. Among them, the more environmentally friendly method of hydrogen production by electrolysis of water has great prospects. At present, the devices for preparing hydrogen include alkaline water electrolyzer (AWE) and proton exchange membrane water electrolyzer (PEMWE).

[0003] Traditional alkaline electrolyzers (AWE) are relatively mature and cheap because they do not require precious metal catalysts. They use high-concentration potassium hydroxide (KOH) as an electrolyte and use porous membranes to separate hydrogen and oxygen. Although AWE can produce hydrogen at a low cost, it takes several hours to reach a stable state under actual operation, which makes it difficult to meet the production needs of intermittent renewable energy.

[0004] Fortunately, PEMWE responds very quickly to a high dynamic range, which is ideal for intermittently harvesting renewable energy to produce completely green hydrogen. The "green hydrogen" produced by the proton exchange membrane (PEM) water electrolysis method can effectively fix renewable energy with temporal instability (such as wind power, solar power, tidal power, etc.), and this method is expected to become an important way to "harvest" renewable energy in the future.

[0005] However, due to the need to use precious metal catalysts based on iridium (Ir) or ruthenium (Ru) and pure titanium (Ti) anode electrode plates that are resistant to acid corrosion, the cost of using PEM electrolyzers is very expensive, limiting their large-scale production and use in the field of water electrolysis. The precious metal part of the PEMWE stack includes porous transport layers (PTLs), bipolar plates (BPs) and precious metal catalysts for oxygen evolution reaction (OER) and hydrogen evolution reaction (HER), which account for 82% of the total cost of the stack. Therefore, there is an urgent need to effectively reduce the equipment cost and operating cost of PEM acidic electrolyzers. At the same time, Ti electrodes easily produce a dense passivation film between the precious metal catalysts during the electrolysis of water, increasing the internal resistance of the electrolytic cell. In engineering, gold plating (Au) or plating (Pt) is often used to increase the conductivity of the electrode, making the electrode cost even higher.

[0006] In addition, the usual technical focus of PEMWE is currently on catalyst coated membrane (CCM), in which a conductive Ir- or Ru-based catalyst is coated on a proton exchange membrane. CCM is the core of PEMWE, which transports protons, separates products and catalyzes HER and OER. In the current state-of-the-art PEMWE structure, the actual electrodes (anode and cathode) are physically pressed onto the catalyst layer. However, this structure suffers from a relatively high ohmic resistance and the risk of catalyst peeling off.

[0007] Researchers have conducted extensive research to develop non-precious metal catalysts and anode electrode plates for PEMWE. However, it has been found that cheap transition metals are severely corroded and dissolved in strong acidic media (pH < 2) at high potentials (> 1.6 V vs. RHE). In addition, the application of cheap transition metal materials in PEMWE is limited by their low OER catalytic performance. Therefore, there is an urgent need to develop cheap materials that are both durable and can catalyze in strong acidic media at high applied potentials.

[0008] Stainless steel is a low-cost and relatively mature metal material. It has good corrosion resistance under near-neutral or alkaline conditions and its surface passivation layer has certain catalytic ability. Therefore, it has been widely used in strong alkaline water electrolysis devices.

[0009] Currently, commercial stainless steel is unstable in a strong acidic environment with high external potential and will experience severe corrosion and dissolution in practical PEMWE. Therefore, pure titanium with high corrosion resistance is used as electrodes in most PEMWEs, which greatly increases the cost of the stack.

[0010] Under strong acidic anodic polarization conditions, a small part of stainless steel can have good corrosion resistance through special passivation behavior. However, this part of stainless steel has almost no catalytic ability for water electrolysis. Therefore, in the actual process of water electrolysis, it is still necessary to load expensive nano-precious metal catalysts on the surface of stainless steel to achieve the function of producing hydrogen at a reasonable potential.

[0011] Based on the existing stainless steel, preparing a surface structure with PEM water electrolysis anode catalytic activity is one of the ways to solve the current cost problem of PEM electrolyzers.

[0012] In a research paper by Lemoine et al. (Lemoine K, Gohari-Bajestani Z, Moury R, ​​et al. Amorphous iron–manganese oxyfluorides, promising catalysts for oxygen evolution reaction under acidic media [J]. ACS Applied Energy Materials, 2021, 4 (2): 1173-1181), it is proposed to use a solution thermal decomposition method to prepare a fluorine (F)-doped Mn and Fe-based amorphous nano-oxide particles, and deposit them on FTO conductive glass as the anode of an acidic electrolyzer. The nanoparticles have catalytic ability to electrolyze water under strong acid conditions. However, the anode is not only cumbersome and costly to manufacture, but also cannot be used as an anode of a PEM electrolyzer because FTO conductive glass cannot be used as an electrode or gas diffusion layer (PTL) of a PEM electrolyzer in practical applications.

[0013] Zheng et al.'s research paper (Zheng K, Ren J, Li X, et al. Engineering crystalline CoMP-decorated (M=Mn, Fe, Ni, Cu, Zn) amorphous CoM LDH for high-rate alkaline water splitting [J]. Chemical Engineering Journal, 2022, 441: 136031) reported that a layer of amorphous Co, Fe-based layered double hydroxide modified by crystalline phosphide (P) was prepared in situ on the surface of nickel foam. This surface structure has good electrolytic water anode catalytic performance and stability in a strong alkaline environment, and has certain application prospects in alkaline electrolyzers. However, transition metal layered double hydroxides cannot exist stably in an acidic environment because they contain a large number of alkaline groups. Co, Fe-based layered double hydroxides cannot adapt to the requirements of the acidic environment in PEM electrolyzers.

[0014] et al.'s research paper ( H, Küpper K, Schmidt M, et al. Steel-based electrocatalysts for efficient and durable oxygen evolution in acidic media [J]. Catalysis Science & Technology, 2018, 8 (8): 2104-2116) reported that the iron-nickel (Fe-Ni) alloy was strongly polarized in a strong alkaline lithium hydroxide (LiOH) solution environment to produce hydroxy metal oxides (such as FeOOH and NiOOH) on its surface. The surface products have a certain electrolytic water catalytic ability under acidic conditions and can be directly used as electrode materials for acidic electrolytic cells. However, due to the insufficient stability of the iron-nickel hydroxy metal oxides in acidic conditions, although they have good electrolytic water catalytic activity, the Faraday efficiency drops significantly within 40,000 seconds due to the dissolution reaction during the electrolysis of water. After the surface products dissolve, the overall corrosion rate of the electrode material increases rapidly, so it still cannot meet the requirements for use as an anode for PEM electrolyzers.

[0015] CN114525544A discloses a method for preparing an iridium-ruthenium alloy noble metal nanoparticle catalyst, which solves the current problems of uneven particle size distribution and low alloying degree of iridium-ruthenium alloy nanoparticles through a complex precursor colloid thermal decomposition method, and can be used as an anode catalyst in a very efficient acidic PEM water electrolysis device. However, due to the limited output of precious metals such as iridium and ruthenium, purification and mining are very complicated, and the high cost of the current PEM electrolyzer is an important reason for limiting its large-scale industrialization. The preparation method disclosed in CN114525544A still cannot solve the high cost problem of large-scale PEM electrolysis of hydrogen. Summary of the invention

[0016] Therefore, the purpose of the present invention is to develop a metal material with catalytic activity for water electrolysis and strong acid stability to replace the current precious metal catalysts and pure titanium electrodes for use in acidic PEM electrolyzers, thereby significantly reducing the equipment cost of producing hydrogen using PEM technology.

[0017] After a large number of experimental studies, the inventors of the present invention found that after appropriate surface thermal oxidation of the manganese-containing stainless steel base material, a passivation film with catalytic activity and durability in an acidic environment can be formed on its surface. The stainless steel with such surface modification is used as the anode in PEMWE, which can simultaneously play the role of an anode electrode plate and catalyze OER, thereby greatly reducing the cost of hydrogen production.

[0018] Based on the above findings, the first aspect of the present invention provides an anode for a PEM water electrolyzer, the anode comprising a stainless steel substrate and a layered oxide structure generated in situ on the surface of the stainless steel substrate, wherein the layered oxide structure comprises crystalline manganese oxide and amorphous iron-containing manganese oxide.

[0019] According to the anode provided by the present invention, the thickness of the layered oxide structure may be 100-800 nm.

[0020] In various embodiments of the present invention, the layered oxide structure may include a manganese-poor inner layer and a manganese-rich outer layer. Wherein, the manganese-rich outer layer contains crystalline manganese oxide and amorphous iron-containing manganese oxide. In a preferred embodiment of the present invention, the alloy composition of the stainless steel matrix comprises, by mass fraction: Cr 12%-25%, Mn 15%-25%, Co and / or Ni10%-20%, Si 0-2.5%, and the balance is Fe and unavoidable impurities.

[0021] It should be noted that the unavoidable impurities may include rare earth elements. Because rare earths are almost inevitably contained in iron ore, the content of rare earth elements in the final stainless steel alloy is usually ~0.001% to 0.1%. The present invention does not require special procedures to remove such a small amount of rare earth elements. In some preferred embodiments, the stainless steel matrix contains Co10%-20%, wherein the manganese-poor inner layer may contain cobalt-rich grains and chromium oxide particles. In this embodiment, the "manganese-poor inner layer" may also be referred to as a "cobalt-rich inner layer". Among them, "cobalt-rich" means that the cobalt content in the corresponding layer is higher than the cobalt content in the stainless steel matrix, "manganese-poor" means that the manganese content in the corresponding layer is lower than the manganese content in the stainless steel matrix, and "manganese-rich" means that the manganese content in the corresponding layer is higher than the manganese content in the stainless steel matrix.

[0022] The inventors have found through research that the presence of the manganese-rich outer layer and the manganese-poor inner layer plays an important role in the catalytic activity and acid stability of the anode of the present invention, wherein:

[0023] (i) Crystalline manganese oxide in the manganese-rich outer layer can provide excellent OER catalytic activity. However, previous reports have shown that crystalline manganese oxide has poor stability in acidic environments, and significant activity loss occurs after only a short period of water electrolysis for 4 hours. Surprisingly, in the anode of the present invention, the amorphous iron manganese oxide present in the manganese-rich outer layer can simultaneously protect the stainless steel matrix and the crystalline manganese oxide from being dissolved. In other words, the combination of amorphous iron manganese oxide in the manganese-rich outer layer and crystalline manganese oxide ensures the stability and OER activity of the anode of the present invention in strongly acidic media. In addition, the present invention also found that iron-containing amorphous manganese oxide may also play an important role in improving the overall OER activity of the surface layered oxide structure, because of the presence of iron in multiple valence states in the disordered structure.

[0024] (ii) For the manganese-poor inner layer, since manganese is the most critical passivation element for the stainless steel substrate under high applied potential, the stability of the manganese-poor layer becomes a decisive factor in the expected life of the surface layered oxide structure and the durability of the entire anode. Surprisingly, the inventors of the present invention found that the manganese-poor inner layer (or cobalt-rich inner layer) between the stainless steel substrate and the manganese-rich outer layer remains intact after water electrolysis, and can effectively prevent the failure of the surface layered oxide structure even when most of the chromium oxide is dissolved. Therefore, Co within the content range required by the present invention separates the stainless steel substrate from the manganese-rich outer layer by forming a cobalt-rich manganese-poor inner layer, avoiding the local resistance increase caused by severe oxidation and improving the stability of the surface layered oxide structure during the OER process.

[0025] According to the anode provided by the present invention, the thickness of the manganese-rich outer layer may be 50-300 nm. In various embodiments of the present invention, the volume percentage of the crystalline manganese oxide in the manganese-rich outer layer is 70%-90%.

[0026] According to the anode provided by the present invention, the thickness of the manganese-poor inner layer can be 100-500 nm. In various embodiments of the present invention, the manganese content in the manganese-poor inner layer is less than 10 wt %. In various embodiments of the present invention, the volume percentage of the chromium oxide (Cr3O) in the manganese-poor inner layer is 30%-60%.

[0027] According to the anode provided by the present invention, the anode generates a current greater than 0.5 mA / cm at a potential above 1.65 V vs. SHE. 2 Oxygen evolution current density. Preferably, the anode of the present invention can withstand a potential range of 1.60V to 1.73V vs. SHE under the oxygen evolution reaction, and an oxygen evolution current density range of 0.1 mA / cm 2 ~5mA / cm 2Considering the service life and effect, the potential of 1.65V to 1.70V vs. SHE is the best range.

[0028] According to the anode provided by the present invention, the time for which the anode maintains a stable oxygen evolution current density under acidic water electrolysis conditions is at least 100 hours, such as 100 to 1000 hours.

[0029] According to the anode provided by the present invention, the alloy component of the stainless steel matrix provides the required metal elements for the surface layered oxide structure involved in the present invention, and is therefore a key factor in achieving OER catalytic activity and acid stability. The role of the Cr element is to form a dense passivation film under air conditions to protect the substrate material from corrosion and oxidation under atmospheric conditions. If the Cr element is less than 12%, a complete and dense passivation film cannot be formed; the role of the Mn element is to generate a passivation film under high potential (~1400mV vs.SHE) conditions to protect the material from corrosion. At the same time, the Mn element is also the most important metal component of the surface structure involved in the present invention. If the Mn element is less than 15%, a surface oxide layer of sufficient thickness may not be formed, and a passivation film sufficient to protect the substrate material at high potential cannot be formed; the role of the Si element is to control the influence of impurities in smelting on the corrosion performance of the material; the Co element can improve the catalytic efficiency of the electrode material under strong acidic conditions. If water is electrolyzed under weak acidic conditions, it can be partially or completely replaced by the Ni element.

[0030] The second aspect of the present invention provides a method for preparing the above-mentioned anode for a PEM water electrolyzer, the preparation method comprising heating a stainless steel substrate to 500-600°C in air and keeping it warm for 10-30 hours to in-situ generate a layered oxide structure on the surface of the stainless steel substrate, wherein the layered oxide structure comprises crystalline manganese oxide and amorphous iron-containing manganese oxide.

[0031] In a preferred embodiment of the present invention, the alloy composition of the stainless steel substrate comprises, by mass fraction, Cr 12%-25%, Mn 15%-25%, Co and / or Ni 10%-20%, Si 0-2.5%, and the balance is Fe and unavoidable impurities.

[0032] The selected holding time is 10 hours to 30 hours to obtain a relatively stable surface oxide layer thickness and structure. In addition, the material surface needs to be kept clean and dry during the preparation process, which is conducive to forming a dense and uniform surface structure.

[0033] In some embodiments of the present invention, the preparation method may further include connecting the anode to an electrolytic cell using a three-electrode method, and then passivating the anode at a potential of 1.4 to 1.5 V vs. SHE.

[0034] The third aspect of the present invention provides a method for regenerating the above-mentioned failed anode, the method comprising: removing the layered oxide structure on the surface of a stainless steel substrate by grinding or ultrasonic cleaning, and then heating the stainless steel substrate to 500-600°C in air and keeping it warm for 10-30 hours to in-situ generate a layered oxide structure on the surface of the stainless steel substrate, wherein the layered oxide structure comprises crystalline manganese oxide and amorphous iron-containing manganese oxide.

[0035] According to the regeneration method provided by the present invention, the present invention does not particularly limit the standard of whether the anode fails, and can be controlled and adjusted in a wide range according to the specific application scenario. For example, it can be determined by setting the time of the water electrolysis reaction, or by monitoring the catalytic current decrease ratio. In some embodiments, the anode can be determined to be failed after 100 hours of water electrolysis reaction, and the regeneration method of the present invention can be applied to regenerate it. In other embodiments, the anode can be determined to be failed by monitoring that the catalytic current drops by 80%, and the regeneration method of the present invention can be applied to regenerate it.

[0036] The inventors of the present invention have found that after more than 100 hours of stable water electrolysis reaction, the catalytic current of the surface structure with catalytic effect involved drops by more than 80%, however, this failure can be completely restored to the original state of anode catalytic activity by re-heat treatment. In this way, the anode provided by the present invention can be recycled, has strong sustainability in practical application, and has the potential to be a core component of an acid electrolyzer.

[0037] A fourth aspect of the present invention provides a PEM water electrolyzer, wherein the anode of the PEM water electrolyzer comprises the anode provided by the present invention, the anode prepared according to the preparation method provided by the present invention, or the anode obtained according to the regeneration method provided by the present invention.

[0038] Compared with the prior art, the PEM water electrolyzer anode provided by the present invention has the following advantages:

[0039] (1) No additional corrosion-resistant matrix material is required, catalyst-electrode integration is achieved, and the resistance problem between the traditional membrane electrode and the gas diffusion layer is overcome.

[0040] (2) The composition and structure of the oxide layer are very simple and can be prepared directly based on bulk materials, avoiding the problems of traditional nanoparticle catalysts such as dispersibility, conductivity, complex preparation process and difficulty in mass production.

[0041] (3) The surface structure can remain stable for a long time under strong acid conditions and can be easily regenerated, solving the problem of insufficient stability of traditional non-precious metal catalysts.

[0042] (4) Compared with precious metal catalysts, this oxide layer structure can significantly reduce the stack cost and maintenance cost of the PEM electrolyzer while having a certain catalytic ability.

[0043] (5) The surface structure prepared by the present invention is suitable for the anode environment of an acidic electrolyzer, and is convenient for combining with proton exchange membrane (PEM) technology. Compared with traditional alkaline electrolyzers, it can more effectively combine renewable energy. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] The embodiments of the present invention are described in detail below with reference to the accompanying drawings, wherein:

[0045] Figure 1 These are SEM images of the stainless steel surface before and after air heat treatment and after 20 hours of water electrolysis in Example 1.

[0046] Figure 2 The cross-sectional HAADF-STEM image and corresponding EDS spectrum results of SS-Co-550 prepared in Example 1.

[0047] Figure 3 The TEM image (a) of the surface structure of the SS-Co-550 sample prepared in Example 1 before water electrolysis, as well as the HRTEM image (b) of the manganese-rich layer and the HRTEM image (c) of the manganese-poor layer are shown.

[0048] Figure 4 Based on Figure 3 (b) Fourier transform image, (a) shows Mn2O3 crystal; (b) shows amorphous FeMnO x .

[0049] Figure 5 The cross-sectional HAADF-STEM image and corresponding EDS spectrum results of SS-Co-550 prepared in Example 1 after electrolysis of water for 20 hours.

[0050] Figure 6 LSV curves (a) and PS polarization curves (b) of the homogenized stainless steel (SS-Co) and the modified stainless steel (SS-Co-550) thermally oxidized in air at 550°C for 20 hours in Example 1.

[0051] Figure 7 (a) shows the Tafel slope of SS-Co and SS-Co-550, and (b) shows the EIS graph of SS-Co and SS-Co-550.

[0052] Figure 8Comparison of the constant potential polarization curves of SS-Co and SS-Co-550 in Example 1 (polarization potential: 1.65 V vs. SHE).

[0053] Fig. 9 The electrolysis was carried out in 0.1 M HClO4 using an argon-protected sealed H-type proton exchange membrane (PEM) assisted electrolysis cell at 0.75 mA / cm 2 The volume of oxygen generated by the SS-Co-550 electrode prepared in Example 1 under a constant current density of .

[0054] Fig.10 This is the constant potential curve of SS-Co-550 in Example 1. DETAILED DESCRIPTION

[0055] The present invention is further described in detail below in conjunction with specific embodiments. The given examples are only for illustrating the present invention, but not for limiting the scope of the present invention.

[0056] Description of the raw materials and methods in the examples

[0057] The concentrated perchloric acid (65 wt.%), ethanol and acetone used were all commercially available analytically pure products. All electrolytes were prepared using deionized water with a resistivity of 18.2 MΩ.

[0058] In the examples, vacuum induction melting was used to prepare stainless steel samples of different compositions. All raw materials used in casting were commercially available single elements. The ingots were homogenized at 1200°C for two hours and then forged into plates with a thickness of 10 mm. All samples were cut from the homogenized plates with a size of 10×10×2 (mm 3 The cut samples were homogenized at 1200°C for two hours and then water quenched to obtain a uniform distribution of alloying elements.

[0059] Example 1

[0060] (1) The alloy composition of the stainless steel matrix material is as follows by mass fraction: Cr 20%, Mn 20%, Co 20%, Si2%, and iron as the balance element.

[0061] (2) Before surface modification of the stainless steel, the stainless steel is homogenized to uniformly distribute the alloying elements of the material to obtain the best surface modification effect. The specific process is: the stainless steel is heated to 1200°C in an argon atmosphere, kept at this temperature for 2 hours, and then quenched.

[0062] (3) After rapid cooling, surface grinding and drying, the homogenized stainless steel is placed in a muffle furnace, heated to 550° C. in air, and kept warm for 20 hours.

[0063] (4) After the heat preservation is completed, the stainless steel is taken out and placed in a room temperature environment to cool naturally. The surface of the stainless steel presents a uniform dark blue or light gray color, indicating that the surface modification is completed. The average thickness of the surface layered oxide structure is 150 to 200 nm.

[0064] (5) The surface-modified stainless steel material is placed in an electrolytic cell, 0.1 M perchloric acid is used as the electrolyte, and a three-electrode method is used, with the surface-modified stainless steel as the working electrode (anode), the calomel electrode as the reference electrode, and the platinum electrode as the counter electrode. The stainless steel electrode is "passivated" at a potential of 1.4 V vs. SHE.

[0065] The current was extremely low (below 100 μA) at 1.50 V vs. SHE, indicating that the stainless steel material was stable and could be used as an anode in an acidic electrolytic cell.

[0066] The anodic polarization potential was then increased to 1.50 V vs. SHE, at which the stainless steel electrode began to undergo oxygen evolution reaction with a current density of approximately 2 mA / cm 2 At the same time, hydrogen bubbles can be observed on the platinum electrode. The stainless steel electrode maintains a stable oxygen evolution current density under acidic water electrolysis conditions for more than 100 hours.

[0067] Example 2

[0068] (1) The alloy composition of the stainless steel matrix material is as follows by mass fraction: Cr 13%, Mn 25%, Co 12%, Si2%, and iron as the balance element.

[0069] (2) Before surface modification of the stainless steel, the stainless steel is homogenized to uniformly distribute the alloying elements of the material to obtain the best surface modification effect. The specific process is: the stainless steel is heated to 1200°C in an argon atmosphere, kept at this temperature for 2 hours, and then quenched.

[0070] (3) After the cooled stainless steel is surface-polished and dried, it is placed in a muffle furnace and heated to 600°C in air for 15 hours.

[0071] (4) After the heat preservation is completed, the stainless steel is taken out and placed at room temperature to cool naturally. The surface of the stainless steel presents a uniform dark blue or dark gray color, indicating that the surface modification is completed. The average thickness of the surface layered oxide structure is 200 to 250 nm.

[0072] (5) The surface-modified stainless steel material was placed in an electrolytic cell, 0.05 M sulfuric acid was used as the electrolyte, and the three-electrode method was used, with the surface-modified stainless steel as the working electrode (anode), the calomel electrode as the reference electrode, and the platinum electrode as the counter electrode. The stainless steel electrode was "passivated" at a potential of 1.45 V vs. SHE.

[0073] The current was extremely low (below 100 μA) at 1.45 V vs. SHE, indicating that the stainless steel material was stable and could be used as an anode in an acidic electrolytic cell.

[0074] The anodic polarization potential was then increased to 1.65 V vs. SHE, at which the stainless steel electrode began to undergo oxygen evolution reaction with a current density of approximately 1 mA / cm 2 At the same time, hydrogen bubbles can be observed on the platinum electrode. The stainless steel electrode maintains a stable oxygen evolution current density under acidic water electrolysis conditions for more than 100 hours.

[0075] Example 3

[0076] (1) The alloy composition of the stainless steel matrix material is as follows by mass fraction: Cr 20%, Mn 20%, Ni 20%, Si2%, and iron as the balance element.

[0077] (2) Before surface modification of the stainless steel, the stainless steel is homogenized to uniformly distribute the alloying elements of the material to obtain the best surface modification effect. The specific process is: the stainless steel is heated to 1200°C in an argon atmosphere, kept at this temperature for 2 hours, and then slowly cooled with the furnace.

[0078] (3) After the cooled stainless steel is surface-polished and dried, it is placed in a muffle furnace and heated to 500°C in air for 30 hours.

[0079] (4) After the heat preservation is completed, the stainless steel is taken out and placed at room temperature to cool naturally. The surface of the stainless steel presents a uniform dark blue or dark gray color, indicating that the surface modification is completed. The average thickness of the surface layered oxide structure is 200 to 250 nm.

[0080] (5) The surface-modified stainless steel material was placed in an electrolytic cell, 0.05 M sulfuric acid was used as the electrolyte, and the three-electrode method was used, with the surface-modified stainless steel as the working electrode (anode), the calomel electrode as the reference electrode, and the platinum electrode as the counter electrode, and the stainless steel electrode was "passivated" at a potential of 1.40 V vs. SHE.

[0081] The current was extremely low (below 100 μA) at 1.40 V vs. SHE, indicating that the stainless steel material was stable and could be used as an anode in an acidic electrolytic cell.

[0082] The anodic polarization potential was then increased to 1.65 V vs. SHE, at which the stainless steel electrode began to undergo oxygen evolution reaction with a current density of approximately 0.7 mA / cm 2 At the same time, hydrogen bubbles can be observed on the platinum electrode. The stainless steel electrode maintains a stable oxygen evolution current density under acidic water electrolysis conditions for more than 100 hours.

[0083] Comparative Example 1

[0084] (1) A stainless steel with alloy composition different from that of the present invention is selected as the base material. The selected stainless steel is super stainless steel 254SMO, and its alloy composition is as follows by mass fraction: Cr 20%, Ni 18%, Mo 6.5%, N 0.2%, and iron is the balance element.

[0085] (2) The stainless steel is homogenized, and the specific process is as follows: the stainless steel is heated to 1200° C. in an argon atmosphere, kept at this temperature for 2 hours, and then slowly cooled in the furnace.

[0086] (3) After the stainless steel is cooled, the surface is polished and dried, and then placed in a muffle furnace, heated to 550°C in air, and kept warm for 20 hours. After being taken out and cooled, it is placed in an electrolytic cell, using 0.1M perchloric acid as the electrolyte, using the three-electrode method, with the stainless steel as the working electrode (anode), the calomel electrode as the reference electrode, and the platinum electrode as the counter electrode.

[0087] (4) Using linear sweep voltammetry, scanning from 0.50 V to 1.70 V vs. SHE at a rate of 10 mV / s, it was found that the stainless steel anode showed severe over-passivation corrosion at a potential of about 1.20 V, and no oxygen was produced when the potential reached above 1.65 V vs. SHE.

[0088] The above phenomenon shows that if the alloy composition of the stainless steel substrate is out of the range required by the present invention, severe over-passivation corrosion will occur under high potential conditions and it is completely unsuitable to be used as a stable anode material for an acid electrolytic cell.

[0089] Comparative Example 2

[0090] (1) The same stainless steel as in Example 1 was selected as the base material.

[0091] (2) Before surface modification of stainless steel, it is homogenized to make the alloy elements of the material evenly distributed to obtain the best surface modification effect. The specific process is: the stainless steel is placed in an argon atmosphere and heated to 1200°C, kept at this temperature for 2 hours, and then quenched.

[0092] (3) After rapid cooling, surface grinding and drying, the homogenized stainless steel is placed in a muffle furnace, heated to 400°C in air, and kept warm for 20 hours.

[0093] (4) After the heat preservation is completed, the stainless steel is taken out and placed in a room temperature environment to cool naturally. The surface of the stainless steel presents a uniform light gold color, and the average thickness of the surface oxide layer is less than 50 nm.

[0094] (5) The surface-modified stainless steel material is placed in an electrolytic cell, 0.1 M perchloric acid is used as the electrolyte, and a three-electrode method is used, with the surface-modified stainless steel as the working electrode (anode), the calomel electrode as the reference electrode, and the platinum electrode as the counter electrode. The stainless steel electrode is "passivated" at a potential of 1.45 V vs. SHE.

[0095] The current is extremely low (below 100 μA) under the condition of 1.45 V vs. SHE, indicating that the stainless steel material is stable and can be used as an anode in an acid electrolytic cell.

[0096] The anodic polarization potential was then increased to 1.70 V vs. SHE. At this potential, oxygen evolution reaction began to occur at the stainless steel electrode, with a maximum current density of about 2 mA / cm 2 At the same time, hydrogen bubbles can be observed on the platinum electrode.

[0097] The light gold oxide layer on the surface of the stainless steel anode completely dissolved within 10 minutes, and the current density dropped rapidly to 100 μA / cm 2 Below, no bubbles are generated on the surfaces of both the cathode and cathode at the same time.

[0098] The above phenomenon shows that if the temperature used for surface modification does not meet the range described in the present invention, the resulting surface oxide layer has poor structural stability and cannot stably play a role in catalysis and hydrogen production under acidic water electrolysis conditions.

[0099] Characterization of surface oxide structure morphology and acid stability

[0100] (1) SEM characterization

[0101] The surface of the stainless steel in Example 1 was characterized by SEM before and after modification (i.e., air heat treatment) and after electrolysis of water for 20 hours. The results are as follows: Figure 1 As shown. Among them, Figure 1 Figure (a) is the SEM image of the stainless steel surface (denoted as SS-Co) before modification after grinding; Figure (b) is the SEM image of the stainless steel surface (denoted as SS-Co-550) after modification; Figure (c) is the SEM image of the stainless steel surface in 0.1M perchloric acid at 0.75mA / cm 2SEM image of the stainless steel surface after 20 hours of water electrolysis; (d) Enlarged view of the rectangular area in (c).

[0102] Figure 1 The evolution of the surface morphology of SS-Co and SS-Co-550 samples is shown. Compared with the smooth surface of the polished SS-Co sample ( Figure 1 Compared with (a), the surface of SS-Co-550 is relatively rough and covered with irregularly distributed nanoparticles ( Figure 1 (b) Figure), these particles may become active sites for OER. However, at such a high polarization potential, most non-precious metals (such as chromium, iron and nickel) are easily dissolved or passivated in acid. Due to the presence of a large amount of unstable transition metal elements in the SS-Co matrix, only a portion of the potential active sites can exist in the acidic water electrolysis environment. Fortunately, manganese oxides can maintain a high potential of up to ~1.70V vs. SHE, and the passivation of manganese can protect the matrix from continued corrosion. Figure 1 As shown in Figure (c), after 20 hours of water electrolysis, the surface was significantly reconstructed by selectively dissolving unstable substances, presenting a smoother morphology. Figure 1 Figure (d) shows Figure 1 (c) The enlarged image of the rectangular area shows dense nanoparticles of different sizes, which means that the surface species undergo a gradual transformation during water electrolysis. Therefore, it can be expected that the OER current density will gradually decrease during long-term water electrolysis of the SS-Co-550 anode due to the partial dissolution of the surface structure.

[0103] (II) High-angle annular dark field scanning transmission electron microscopy (HAADF-STEM) characterization

[0104] The surface structure of SS-Co-550 prepared in Example 1 was further characterized by HAADF-STEM. Figure 2 As shown. Among them, Figure 2 (a) HAADF-STEM image, Figure 2 (b) shows the EDS element energy spectrum results corresponding to Figure .

[0105] Figure 2 The HAADF image in (a) shows that SSCo-550 has a distinct double-layer surface structure before water electrolysis, showing different contrasts, indicating that the element distribution in each layer is significantly different. Figure 2As shown in Figure (b), the corresponding EDS results confirm that the outermost layer (manganese-rich outer layer) with a darker contrast is manganese oxide with a thickness of about 250nm, in which some iron elements are mixed, while the lower layer is a manganese-poor inner layer (cobalt-rich inner layer) with a thickness of about 300nm, in which granular chromium-rich particles are embedded.

[0106] High-resolution TEM images provide more information about the crystallinity and lattice structure of the thermally oxidized surface layer, making it easier to identify the OER-active species and the overall surface reconstruction process.

[0107] Figure 3 Figure (a) shows a TEM image of the surface structure of the SS-Co-550 sample before water electrolysis. Compared with the STEM-HAADF image, this image shows a more obvious diffraction contrast. Specifically, the manganese-rich outer layer contains nanocrystals with different crystal orientations, while Figure 2 This is not shown in Figure (a). The outermost protective layer is composed of sputtered gold-palladium nanoparticles to reduce ion damage to the sample surface and avoid environmental contamination of the sample surface.

[0108] like Figure 3 As shown in Figure (b), the manganese-rich outer layer is composed of a mixture of amorphous and crystalline structures. The fast Fourier transform (FFT) image ( Figure 4 ) confirmed this. Combined with the EDS spectrum results ( Figure 2 (b) According to the FFT pattern and the calculated plane spacing, the crystal structure was determined to be corundum-type MnO 23 Meanwhile, the thinner and highly amorphous part consists of a mixture of iron and manganese oxides.

[0109] exist Figure 3 In Figure (c), the chromium-rich grains in the manganese-poor inner layer are analyzed to be Cr3O, with a space group of Pm-3n(223) and a cubic crystal system. The lattice geometry is In addition, the oxide crystal structure confirmed by microbeam diffraction (not shown) is completely consistent with the FFT pattern. It can be inferred that at the heating temperature of the present invention, the alloying elements chromium and manganese are more susceptible to thermal oxidation. In contrast, at higher heating temperatures (650°C to 800°C), manganese and chromium form a (manganese, chromium) 3O4 spinel structure, which is corrosion resistant but not as active as manganese oxide in OER.

[0110] Figure 5 The cross-sectional HAADF-STEM image and corresponding EDS spectrum results of SS-Co-550 prepared in Example 1 after electrolysis of water for 20 hours.

[0111] exist Figure 5Figure (a) shows the SS-Co-550 sample in 0.1M HClO4 at 0.75mA / cm 2 The STEM-HAADF image after 20 hours of water electrolysis shows a catastrophic change, with obvious porous spaces appearing inside the manganese-poor layer. Combined with the EDS spectrum results ( Figure 5 (b) The porous layer is due to the complete dissolution of the granular Cr3O oxide, while the Mn-poor bcc nanocrystals remain stable after water electrolysis. However, the thin chromium oxide passivation layer also disappears, forming a physical gap between the Mn-rich and Mn-poor layers, which makes the Mn oxide more fragile in terms of structural stability. Despite the presence of a large number of defects in the surface structure, the cobalt-rich layer remains stable and no dissolution is observed, which plays an important role in connecting the substrate and the Mn oxide layer. In addition, the Mn oxide layer is also durable and its thickness is almost the same as before water electrolysis (refer to Figure 2 (a) Figure ).

[0112] Characterization of OER catalytic activity

[0113] (I) Electrochemical measurement

[0114] The acidic environment anodic polarization curves of the homogenized stainless steel (SS-Co) in Example 1 and the modified stainless steel (SS-Co-550) thermally oxidized in air at 550°C for 20 hours were measured to compare the electrochemical OER catalytic activities of the two. Figure 6 LSV curves (a) and PS polarization curves (b) of the homogenized stainless steel (SS-Co) and the modified stainless steel (SS-Co-550) thermally oxidized in air at 550°C for 20 hours in Example 1.

[0115] Figure 6 Figure (a) shows the linear sweep voltammetry (LSV) curves of stainless steel before and after modification. Due to the dual passivation effect of chromium and manganese, both the original SS-Co and the modified SS-Co-550 have remarkable corrosion resistance from low potential to high potential in acid. The sudden increase in current density on the LSV curve indicates that oxygen begins to be produced, which intuitively represents the starting point of hydrogen generation on the counter electrode. Compared with the SS-Co electrode, SS-Co-550 has higher OER performance in terms of starting potential and OER current density, indicating that its energy efficiency and hydrogen generation rate are improved, respectively. The small peak between 1.0V and 1.1V represents the transient passivation corrosion of chromium, which is quickly protected by the passivation effect of manganese.

[0116] Figure 6Figure (b) shows the steady-state current density of stainless steel before and after modification at different external potentials. At a polarization potential of 1.40 V, the current density of the original SS-Co is extremely low due to the passivation of manganese, indicating that the stainless steel matrix is ​​well protected and has almost no OER activity. After increasing the external potential to 1.45 V, the OER current density of SS-Co reaches 0.27 mA / cm 2 In contrast, the modified SS-Co-550 has a stable current density of 0.75 mA / cm at 1.40 V and 1.45 V, respectively. 2 and 2.0mA / cm 2 , which is almost one order of magnitude higher than that of the original SS-Co electrode. The steady-state current density is in good agreement with the LSV result, verifying the non-steady-state polarization curve.

[0117] Figure 7 (a) shows the Tafel slope of SS-Co and SS-Co-550, (b) shows the EIS graph of SS-Co and SS-Co-550, with a fluctuation amplitude of 10 mV, from 100,000 Hz to 0.1 Hz, X-axis (Z'), real part; Y-axis (-Z"), imaginary part.

[0118] Figure 7 Figure (a) is from Figure 6 The curve intercepted from the LSV curve of (a) shows that the OER activity of the modified SS-Co-550 anode is significantly improved. SS-Co-550 reaches 1mA / cm 2 The overpotential required for the OER current density is 516 mV, which is lower than that of SS-Co (565 mV). In addition, the Tafel slope of SS-Co-550 (62.1 mV-dec -1 ) is lower than the Tafel slope of SS-Co (89.3mV-dec -1 ) is high, which leads to a larger difference in current density at higher external potentials. The changes between the Tafel slope and the overpotential indicate different mechanisms with different electron transfer processes and kinetic characteristics, which are believed to be caused by some OER catalytic species formed on the surface of SS-Co-550. Figure 7(b) shows the electrochemical impedance spectroscopy (EIS) spectra (Nyquist plots) of SS-Co and SS-Co-550 at voltages of 1.40 V and 1.45 V. The Nyquist plot can be explained by an equivalent circuit consisting of solution resistance (Rs), charge transfer resistance (Rct), and double layer capacitance (Cdl). As the external potential increases, the charge transfer resistance decreases due to the enhanced driving force. In addition, at the same potential, the equivalent resistance of SS-Co-550 is significantly lower than that of pristine SS-Co, indicating a lower energy barrier for electron transfer at the interface. Therefore, at the same external potential, SS-Co-550 shows better OER activity and produces a higher current density.

[0119] Figure 8 The constant potential polarization curves of the surface structure of the present invention and the base material are compared (polarization potential: 1.65 V vs. SHE). The results show that after the surface modification of the present invention, the current density is increased by an order of magnitude.

[0120] (II) Gas chromatography measurement

[0121] Side reactions at the anode during water electrolysis, which have long been a concern, are usually caused by corrosion and the formation of hydrogen peroxide. Fig. 9 As shown, the present invention measured the amount of oxygen produced on the SS-Co-550 anode by gas chromatography. The results show that the average Faradaic efficiency of the SS-Co-550 anode exceeds 99%, and after 4 hours of continuous operation, the Faradaic efficiency remains at 97.5%, indicating that the SS-Co-550 anode has excellent stability and reliable OER catalytic performance. Slow corrosion of the substrate or partial dissolution of the OER active surface layer may cause a slight decrease in the Faradaic efficiency.

[0122] According to electrochemical and gas chromatography measurements, the surface layered oxide structure formed by thermal oxidation of SS-Co is not only catalytically active for OER but also stable and highly selective in harsh oxidative and corrosive environments.

[0123] Regeneration of OER catalytic activity

[0124] Fig.10 This is the constant potential curve of SS-Co-550. After maintaining for more than 100 hours, the hydrogen production current decreases. The electrode can be completely restored to its original activity and stability by surface cleaning and re-heat treatment.

[0125] pass Fig.10It can be seen from the results that the OER catalytic activity of the anode of the present invention is regenerated by heat treatment. The specific method is: first, the surface of the deactivated SS-Co-550 electrode is ultrasonically cleaned or polished in water; then, after drying, it is put back into the muffle furnace and heated using the same process (such as: keeping at 550°C in air for 20 hours), and the activity and stability can be fully restored.

[0126] In the prior art, when the OER current decays to an unacceptable level, reactivating the anode in the water electrolyzer becomes very complicated, thereby invisibly increasing the maintenance costs of long-term operation. Due to the simple heat treatment process of the present invention, the OER activity of stainless steel can be fully restored with simple cleaning and heating steps. In addition, from a sustainable perspective, the discarded stainless steel can also be recycled as raw material for new parts of the water electrolyzer. The present invention not only produces an autocatalytic stainless steel anode that can withstand acidic environments in PEM water electrolyzers, but also provides a sustainable development path for cost-effective hydrogen production by using recyclable stainless steel and a simple regeneration method.

[0127] Characterization and Test Method Description

[0128] The samples used for microstructural characterization were polished after grinding using a single crystal diamond suspension (MetaDi, Buehler) with a particle size of 1 μm. The overall surface morphology of the original and modified samples was observed using a scanning electron microscope (SEM, Zeiss Sigma300). The transmission electron microscope (TEM, Talos F200X) was equipped with a high-angle dark field (HAADF) detector and a Super-XEDS detector to determine the detailed surface structure and local composition changes of the samples. Combined with the EDS results, high-resolution TEM (HRTEM) and microbeam diffraction techniques were used to identify the crystalline information of the surface material. The specimens used for TEM identification were prepared by lifting from the surface area of ​​the sample using a focused ion beam (FIB).

[0129] All electrochemical measurements were performed at room temperature using an electrochemical workstation (PARSTAT 3000A, Princeton Applied Research). The cell used consisted of three electrodes, including a working electrode, a saturated calomel electrode (SCE) reference electrode, and a platinum sheet counter electrode. All surfaces of the test samples were polished with silicon carbide papers of 240, 800, 1200, and 2500 grits in sequence and then cleaned with deionized water and ethanol. To avoid crevice corrosion, the test samples were directly welded on pure titanium wires, which were connected to the electrochemical workstation as working electrodes. Linear sweep voltammetry (LSV) measurements were performed in 0.1 M perchloric acid solution without any buffer at a scan rate of 10 mV / s from 0.7 V to 1.7 V vs. SCE. Potentiostatic (PS) measurements were performed in unbuffered 0.1 M perchloric acid solution at an anodic potential of 1.40 V or 1.45 V vs. SCE. The frequency range of the electrochemical impedance spectroscopy (EIS) measurement is 0.1 Hz to 100 kHz, and the AC amplitude is 10 mV. Unless otherwise specified, the potential value in the present invention is based on a saturated calomel electrode (SCE).

[0130] Electrostatic (GS) measurements were performed in a sealed H-type cell with the anodic and cathodic compartments separated by a Nafion 117 proton exchange membrane (DuPont). Water was charged at 0.75 mA / cm in 0.1 M perchloric acid electrolyte. 2 Oxygen and hydrogen were produced by electrolysis at a constant current density of . The produced hydrogen and oxygen were analyzed by gas chromatography (Fuli Analytical Instrument, GC9790 Plus). Argon was passed into a sealed H-type chamber for 30 minutes to eliminate the target gas in the air. 2 ml of gas in each sample chamber was tested every hour to obtain the peak area of ​​oxygen and hydrogen. Argon was used as a carrier gas.

[0131] The present invention proposes an OER active surface structure based on stainless steel, which is prepared by a simple heat treatment in air at 550°C. Compared with the untreated stainless steel, the OER current density of the surface modified stainless steel is increased by an order of magnitude. At the same time, at 0.75 mA / cm 2 After 4 h of water electrolysis, the Faradaic efficiency remained at 97.5%. The improvement in OER catalytic activity is attributed to the formation of a manganese-rich layer on the surface, which is rich in MnO 23 A mixture of crystalline and amorphous iron-containing manganese oxides. The modified stainless steel anode can be maintained in 0.1M perchloric acid for more than 100 hours before being completely deactivated. The decay of the OER current is mainly caused by the anodic dissolution of chromium oxides under high external potentials and the direct stripping of surface manganese-based catalytic substances. Due to the advantages of high cost-effectiveness, recyclability and easy reactivation, the self-catalytic bulk stainless steel anode is expected to be able to design cheap catalytic stainless steel electrodes for PEM water electrolyzers.

Claims

1. An anode for a PEM water electrolyzer, the anode comprising a stainless steel substrate and a layered oxide structure generated in situ on the surface of the stainless steel substrate, wherein: The layered oxide structure includes crystalline manganese oxide and amorphous iron-containing manganese oxide.

2. The anode according to claim 1, wherein The thickness of the layered oxide structure is 100-800 nm.

3. The anode according to claim 1, wherein The layered oxide structure includes a manganese-poor inner layer and a manganese-rich outer layer.

4. The anode according to claim 3, wherein The manganese-rich outer layer comprises crystalline manganese oxide and amorphous iron-containing manganese oxide.

5. The anode according to claim 3, wherein The volume percentage of the crystalline manganese oxide in the manganese-rich outer layer is 70% to 90%.

6. The anode according to claim 3, wherein The thickness of the manganese-rich outer layer is 50 to 300 nm.

7. The anode according to claim 3, wherein The thickness of the manganese-poor inner layer is 100-500 nm.

8. The anode according to claim 1, wherein The alloy components of the stainless steel matrix include, by mass fraction, Cr 12%-25%, Mn 15%-25%, Co and / or Ni 10%-20%, Si 0-2.5%, and the remainder is Fe and inevitable impurities.

9. The anode according to claim 3, wherein The manganese-poor inner layer comprises chromium oxide particles, and cobalt-rich grains and / or nickel-rich grains.

10. The anode according to claim 3, wherein The manganese content in the manganese-poor inner layer is less than 10 wt %.

11. The anode according to claim 9, wherein The volume percentage of the chromium oxide in the manganese-poor inner layer is 30% to 60%.

12. The anode according to any one of claims 1 to 11, wherein The anode generates more than 0.5 mA / cm at a potential above 1.65 V vs. SHE. 2 Oxygen evolution current density.

13. The anode according to any one of claims 1 to 11, wherein The anode has an oxygen evolution current density range of 0.1 mA / cm at a potential of 1.60 V to 1.73 V vs. SHE. 2 ~5mA / cm 2 .

14. The anode according to any one of claims 1 to 11, wherein The anode maintains a stable oxygen evolution current density for at least 100 hours under acidic water electrolysis conditions.

15. The method for preparing an anode for a PEM water electrolyzer according to any one of claims 1 to 14, comprising heating a stainless steel substrate to 500-600° C. in air and keeping the temperature for 10-30 hours to in-situ generate a layered oxide structure on the surface of the stainless steel substrate, wherein: The layered oxide structure includes crystalline manganese oxide and amorphous iron-containing manganese oxide.

16. The preparation method according to claim 15, wherein: The alloy components of the stainless steel matrix include, by mass fraction, Cr 12%-25%, Mn 15%-25%, Co and / or Ni 10%-20%, Si 0-2.5%, and the balance Fe and inevitable impurities.

17. The preparation method according to claim 15, wherein: The layered oxide structure includes a manganese-poor inner layer and a manganese-rich outer layer, wherein the manganese-rich outer layer contains crystalline manganese oxide and amorphous iron-containing manganese oxide.

18. The preparation method according to claim 17, wherein: The volume percentage of the crystalline manganese oxide in the manganese-rich outer layer is 70% to 90%.

19. A method for regenerating a failed anode, wherein the anode is the anode for a PEM water electrolyzer according to any one of claims 1 to 14, the method comprising: The layered oxide structure remaining on the surface of the stainless steel substrate is removed by grinding or ultrasonic cleaning, and then the stainless steel substrate is heated to 500-600° C. in air and kept warm for 10-30 hours to in-situ generate a layered oxide structure on the surface of the stainless steel substrate, wherein the layered oxide structure comprises crystalline manganese oxide and amorphous iron-containing manganese oxide.

20. A PEM water electrolyzer, wherein the anode of the PEM water electrolyzer comprises the anode according to any one of claims 1 to 14, the anode prepared according to the preparation method according to any one of claims 15 to 18, or the anode regenerated according to the method according to claim 9.

Citation Information

Patent Citations

  • Preparation method of PEM water electrolysis oxygen evolution catalyst iridium ruthenium alloy

    CN114525544A